Growth responses and genetic variation among highly ecologically diverse spring wheat genotypes grown under seawater stress - Amro, Ahmed; Harb, Shrouk; Farghaly, Khaled A.; Ali, Mahmoud M. F.; Mohammed, Aml G.; Mourad, Amira M. I.; Afifi, Mohamed; Börner, Andreas; Sallam, Ahmed (Frontiers in Plant Science, 2022)
Scanty freshwater resources are used for human activities and agriculture. Moreover, they are expected to be declined due to climate change. Sequentially, they will not be enough for food production in the growing populations. Therefore, irrigating crops with seawater could be an alternative solution. However, very little work has been done on seawater tolerance in wheat. To address this challenge, a set of 80 highly diverse spring wheat genotypes collected from different countries in Europe was tested under 50% seawater stress at the early growth stage. Four seedling shoot and root traits were scored in all genotypes. High genetic variation was found among all genotypes for epicotyl length (EL), hypocotyl length (HL), number of radicles (NOR), and fresh weight (FW). A set of eight genotypes marked with high performance in seedling traits was selected. The correlation analyses revealed highly significant correlations among all traits scored. NOR had the highest correlation with the other seedling traits, and was thought to be an important adaptive trait under seawater treatment. The genetic diversity based on genetic distance was studied among all genotypes. The result of genetic diversity revealed a wide range of genetic distances among all genotypes. The eight selected genotypes showed high genetic distance among them. ATRI 5310 (France) had a high genetic distance from all the other seven genotypes. Such high genetic diversity could be utilized for selecting the highly divergent genotypes for crossing in a future breeding program. The results obtained in this study provide very useful information on the presence of different genetic resources in wheat for seawater tolerance.